Trabeculectomy Revisited - Ali, Syed Imtiaz (Pakistan Journal of Ophthalmology, 2010)
Glaucoma describes a group of eye diseases defined by a degeneration of the optic nerve with typical appearance of the optic nerve head leading to loss of visual function best seen by changes in the visual field. Very often the intraocular pressure (IOP) is increased above normal values. Although this definition has been accepted for quite some time it had been unclear weather or not lowering of IOP would prevent or stop glaucoma1. Mean while two large studies have been conducted to prove that lowering IOP in patients with ocular hypertension can prevent or at least delay the onset of glaucoma2,3.